2009
DOI: 10.1016/j.beth.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Pilot Study of Cognitive-Behavioral Therapy in a Sample of Incarcerated Women With Substance Use Disorder and PTSD

Abstract: This randomized controlled pilot study compared a cognitive-behavioral therapy (Seeking Safety; SS) plus treatment-as-usual (TAU) to TAU-alone in 49 incarcerated women with substance use disorder (SUD) and posttraumatic stress disorder (PTSD; full or subthreshold). Seeking Safety consisted of a voluntary group treatment during incarceration and individual treatment after prison release. TAU was required in the prison and comprised 180 to 240 hours of individual and group treatment over 6 to 8 weeks. Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
1
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(197 citation statements)
references
References 32 publications
3
183
1
5
Order By: Relevance
“…All but one of these studies [12] found no significant between-group difference in PTSD symptom severity following treatment. However, most of these studies did find that PTSD symptom severity significantly decreased following treatment for both the therapeutic group and the nonspecific comparison condition [9,16,25,36]. Nonspecific comparison groups in combination with a wait list comparison group are helpful for interpreting the results of studies in which the treatments being compared do not differ from one another.…”
Section: Comparison Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…All but one of these studies [12] found no significant between-group difference in PTSD symptom severity following treatment. However, most of these studies did find that PTSD symptom severity significantly decreased following treatment for both the therapeutic group and the nonspecific comparison condition [9,16,25,36]. Nonspecific comparison groups in combination with a wait list comparison group are helpful for interpreting the results of studies in which the treatments being compared do not differ from one another.…”
Section: Comparison Groupsmentioning
confidence: 99%
“…Of the 17 studies listed in Tables 1 and 2, 8 used a nonspecific comparison design. Typical nonspecific treatments in these studies included relaxation [12], psychoeducation [25,28], present-centered therapy [9,16], and treatment as usual [36]. All but one of these studies [12] found no significant between-group difference in PTSD symptom severity following treatment.…”
Section: Comparison Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Women's psychosocial problems and needs are well documented in the correctional literature from Scandinavia (Amundsen, 2011;Cramer, 2014;Lindberg, 2005;Mathiassen, 2011;Yourstone et al, 2010), and other countries in Europe and outside Europe (Bartlett et al, 2014;Black et al, 2013;Chen, 2010;Covington, 2008, Leschied, 2011Sacks et al, 2012;Sapouna et al, 2011;Zaplin, 2008;Zlotnick et al, 2008Zlotnick et al, , 2009Van Wormer, 2010). Recently, a Norwegian study demonstrated that one out of four women reported major or moderate depression (Cramer, 2014).…”
Section: Introductionmentioning
confidence: 99%